Gout and the risk of COVID-19 diagnosis and death in the UK Biobank: a population-based study. (April 2022) - Topless, Ruth K; Gaffo, Angelo; Stamp, Lisa K; Robinson, Philip C; Dalbeth, Nicola; Merriman, Tony R
Summary: Background: There is a paucity of data on outcomes for people with gout and COVID-19. We aimed to assess whether gout is a risk factor for diagnosis of COVID-19 and COVID-19-related death, and to test for sex- and drug-specific differences in risk. Methods: We used data from the UK Biobank, which included 15 871 people with gout. We used multivariable-adjusted logistic regression in the following analyses using a case-control study design: to test for an association between gout and COVID-19 diagnosis in the entire UK Biobank cohort (n=459 837); to test for an association between gout and COVID-19-related death in people who were known to have died or survived with COVID-19 (n=15 772); to test for an association between gout and COVID-19-related death in the entire UK Biobank cohort (n=459 837); and to assess risk of COVID-19-related death in a subset of patients from the UK Biobank cohort with prescription data, stratified by prescription of urate-lowering therapy and colchicine (n=341 398). Models 1 and 2 were adjusted for age group, sex, ethnicity, Townsend deprivation index, BMI, and smoking status. Model 2 was also adjusted for diagnosis of 16 other diseases that are established comorbidities of gout or established risk factors for COVID-19-related death. Findings: Gout was associated with diagnosis of COVID-19 (odds ratio [OR] 1·20, 95% CI 1·11–1·29) but not with risk of COVID-19-related death in the cohort of patients diagnosed with COVID-19 (1·20, 0·96–1·51). In the entire cohort, gout was associated with COVID-19-related death (1·29, 1·06–1·56); women with gout had an increased risk of COVID-19-related death (1·98, 1·34–2·94), whereas men with gout did not (1·16, 0·93–1·45). We found no significant differences in the risk of COVID-19-related death according to prescription of urate-lowering therapy or colchicine. When patients with gout were stratified by vaccination status, the risk of diagnosis with COVID-19 was significant in the non-vaccinated group (1·21, 1·11–1·30) but not the vaccinated group (1·09, 0·65–1·85). Interpretation: Gout is a risk factor for COVID-19-related death in the UK Biobank cohort, with an increased risk in women with gout, which was driven by risk factors independent of the metabolic comorbidities of gout. Funding: Health Research Council of New Zealand.